2016
DOI: 10.1002/2015ja022222
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric temperature estimation from meteor decay times during Geminids meteor shower

Abstract: Meteor radar observations at the Sodankylä Geophysical Observatory (67° 22′N, 26° 38′E, Finland) indicate that the mesospheric temperature derived from meteor decay times is systematically underestimated by 20–50 K during the Geminids meteor shower which has peak on 13 December. A very good coincidence of the minimum of routinely calculated temperature and maximum of meteor flux (the number of meteors detected per day) was observed regularly on that day in December 2008–2014. These observations are for a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…The majority of meteor trails are underdense, and moreover, the detection algorithm may reject overdense trails as nonmeteor signals (Hocking et al, ). Nevertheless, some SKiYMET meteor radar detections lasting a few tenths of a second are from overdense trails (Kozlovsky et al, ).…”
Section: Meteor Radar Observationsmentioning
confidence: 99%
“…The majority of meteor trails are underdense, and moreover, the detection algorithm may reject overdense trails as nonmeteor signals (Hocking et al, ). Nevertheless, some SKiYMET meteor radar detections lasting a few tenths of a second are from overdense trails (Kozlovsky et al, ).…”
Section: Meteor Radar Observationsmentioning
confidence: 99%
“…Kozlovsky et al . [] indicated that the temperature estimation from meteor decay times can be severely affected by meteor showers because of the peculiar distribution of the meteor decay time within the meteor showers. However, we found that the effects of meteor showers on the linear relationship between the FWHM and the temperature at 90 km are negligible.…”
Section: Height Distribution Of Meteor Echoesmentioning
confidence: 99%
“…This nearly invariable proportionality constant allows us to estimate the temperature at the meteor peak altitude (~90 km) by using only the FWHM data observed by the meteor radar. Kozlovsky et al [2016] indicated that the temperature estimation from meteor decay times can be severely affected by meteor showers because of the peculiar distribution of the meteor decay time within the meteor showers. However, we found that the effects of meteor showers on the linear relationship between the FWHM and the temperature at 90 km are negligible.…”
Section: Height Distribution Of Meteor Echoesmentioning
confidence: 99%
“…• 38 ′ E, Finland) reported by (Kozlovsky et al, 2016) have indicated that the mesospheric temperature at an average altitude of 91 km is systematically underestimated by 20 − 50 K during the Geminid meteor shower (with the peak activity on the 13 th of December). According to the SGO meteor radar observations and data obtained with the Earth Observing System (EOS) Microwave Limb Sounder (MLS) onboard the NASA Aura satellite during the Geminid meteor shower in 2008−2014 the peak night meteor rate accounted for 15, 000 − 20, 000 mete-ors d −1 .…”
Section: Kinetics Of Interaction Between Meteoric Matter and Ozone Layermentioning
confidence: 98%